Velocidade de infiltração em área pastagem degradada e floresta natural no município de Porto Velho (RO) - Eliomar Pereira da Silva Filho (Confins)
In recent decades large tracts of land in the Amazon, for the pastures have been abandoned due to degradation of its soils. This study evaluated the infiltration rate in a Typic Dystrophic Yellow Latosol (LAd) and a Typic Dystrophic Red-Yellow Argisol (PVAd) in pastures with 20 years of use and natural forests continued the same patches of soil. Were considered for analysis of the effects of grazing on infiltration associated with compaction promoted by the trampling of cattle, in contrast to results obtained in the forest. The work was carried out at Embrapa in Porto Velho-RO, noting variations in the velocity of vertical water infiltration into the soil, using a concentric ring infiltrometer, and using the model of Horton's equation to determine the rate equation of infiltration. We evaluated three points in each environment - forest, pasture - all soils considered. The values of infiltration proved to be 3-4 times faster in the forest in relation to the contents of pasture for PVAd and up to 100 times for LAd.